The Role of Sodium and Glucose in the Prognosis of Patients with Aneurysmal Subarachnoid Hemorrhage: A Literature Review of New Evidence - Dell'Orto, Zeferino Campos; Silveira, Isadora Valério da; França, Larissa da Silva Torres; Medeiros, Murillo Sampaio Ferreira; Gomes, Talita Cardoso; Pinto, Bruno Alves; Oliveira, Daniel Gonçalves de; Lopes, Gabryell Thiengo; Viana, Ivan Magalhães (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
The present study aims to review the influence of glycemia and natremia on the propensity to develop complications, worse prognosis, and mortality risk in patients with aneurysmal subarachnoid hemorrhage (aSAH). This is an integrative literature review guided by the guiding question: “Do changes in blood glucose levels or plasma sodium concentration influence in-hospital morbidity and mortality in patients with aneurysmal subarachnoid hemorrhage?”. The search for articles was performed on the PubMed platform, limiting the selection to works published in English in the period from 2017 to 2022. The results found demonstrate that the role of sodium ions in changes in the prognosis of patients is complex, with hypernatremia being the main factor described to worse outcomes. In contrast, the part of hyponatremia is controversial and may not have prognostic value, and serum sodium concentration is increasingly an important item to be evaluated in patients with aSAH. As for glucose, the variability of this substrate, both hyperglycemia and hypoglycemia, may be correlated with in-hospital and long-term mortality in patients with aSAH. Thus, the present study concludes that changes in blood glucose values and plasma sodium concentration influence the in-hospital morbidity and mortality of patients with aSAH. However, it is emphasized that the analysis of the independent influence of each of the related predictors must be done with caution due to the heterogeneity of the results found.
Keywords: neurosurgery; hemorrhagic stroke; intracranial aneurysm